Changes in physical activity, sedentary behaviour and sleep across the transition from primary to secondary school: A systematic review. Issue 5 (May 2020) - Chong, Kar Hau; Parrish, Anne-Maree; Cliff, Dylan P.; Kemp, Byron J.; Zhang, Zhiguang; Okely, Anthony D.
Abstract: Objectives: To describe how children's time spent in the 24-h movement behaviours of physical activity (PA), sedentary behaviour (SB) and sleep change, individually and collectively, across the transition from primary to secondary school. Design: Systematic review. Methods: Six electronic databases were searched from January 1990 to May 2019. Eligibility criteria included longitudinal studies reporting time spent in PA, SB and/or sleep, with baseline assessments conducted during the last two years of primary school and at least one follow-up during the first two years of secondary school. For studies reporting only SB, this review considered those published from November 2015 onwards to update a previous systematic review. Results: The present review identified six articles that reported changes in PA (n = 5) or PA and SB concurrently (n = 1). Most articles had a high risk of bias (n = 4/6). There was limited but consistent evidence of a change in PA over the school transition period; in particular a decrease in total daily PA and during specific time periods (i.e., in-school, after-school and leisure time). A concurrent but opposite change was observed in SB. No studies were identified that assessed changes in sleep, or all three movement behaviours concurrently. Conclusions: Further research exploring concurrent changes in all movement behaviours (PA, SB and sleep) and associated factors is warranted to inform future behavioural interventions and policies for promoting an optimal 24 h movement behaviour pattern during this critical developmental period.